Synthetic applications of hydrazones - Perry, M; Perry, Matthew William Dampier (1985)
﻿ This thesis describes investigations of reactions of hydrazones and their N-anions via the imino carbon atom; these reactions show umpolung reactivity. The conversion of the derived azo products into synthetically useful compounds (e.g. 4-ketoesters, 4-ketoacids, 4-ketonitriles, alkanes, amines) is also described. Reactions of ṯ-butylhydrazone anions with enoic esters are described. 4-ṯ-Butylazoesters were formed on reaction with methyl crotonate. The 4-ṯ-butylazoesters derived from aldehyde ṯ-butylhydrazones were converted by tautomerisation of the azo function and hydrolysis of the resultant ṯ-butylhydrazone to 4-ketoesters or 4-ketoacids in 47-60% yield. Other Michael type electrophiles investigated gave negligible yields of C-adducts. ṯ-Butylhydrazones of aliphatic aldehydes were found to give ene adducts with methyl acrylate or aerylonitrile on reflux in xylene for 24h. The resultant azo compounds were converted into 4-ketoesters (75-90%) or 4-Ketonitriles (18- 75%) by tautomerisation and hydrolysis. Other potential enophiles investigated did not give C-adducts. <a a="" acid="" addition="" aldehyde="" an="" and="" benzaldehyde="" butylhydrazone="" by="" dehydrative="" described.="" described.<="" elimination="" from="" is="" of="" p="" reduction="" synthesis="" the="" with="" zinc-acetic="" ṯ-="" ṯ-butylazoalkene="" ṯ-butylazoalkenes=""> The C-alkylation of tritylhydrazone anions with alkyl halides gave tritylazoalkanes. Tritylazoalkanes decomposed by homolytic fragmentation with dinitrogen evolution above -20°C. Trapping with ethanethiol of the resultant radicals gave alkanes in 27-69% yield. The last section describes investigations of the anions of various secondary alkyl hydrazones for C-reaction, and attempted reduction of the resultant azoalkanes to amines Isopropyl- and cyclohexylhydrazones gave low yields of Cadducts. 2,4-Dimethylpent-3-yl- (DMP) and 3,3-dimethylbut- 2-ylhydrazones (TBM) gave good yields of C-adducts. Direct reduction of the azoalkanes to amines was not achieved Azoalkanes derived by alkylation of ketone DMP or TBM hydrazones were tautomerised and hydrolysed to hydrazines in low yield. Reduction of a so-formed hydrazine gave an amine, but in low overall yield (14%).